Fall risk in people with MS: A Physiological Profile Assessment study. (1st April 2016) - Hoang, Phu D; Baysan, Meryem; Gunn, Hilary; Cameron, Michelle; Freeman, Jenny; Nitz, Jennifer; Low Choy, Nancy L; Lord, Stephen R
Introduction: The Physiological Profile Assessment (PPA) is used in research and clinical practice for assessing fall risk. We compared PPA test performance between people with multiple sclerosis (MS) and healthy controls, determined the fall-risk profile for people with MS and developed a reference database for people with MS. Methods: For this study, 416 ambulant people with MS (51.5 ± 12.0 years) and 352 controls (52.8 ± 12.2 years) underwent the PPA (tests of contrast sensitivity, proprioception, quadriceps strength, reaction time and sway) with composite fall-risk scores computed from these measures. MS participants were followed prospectively for falls for 3 months. Results: The MS participants performed significantly worse than controls in each PPA test. The average composite fall-risk score was also significantly elevated, indicating a "marked" fall risk when compared with controls. In total, 155 MS participants (37.3%) reported 2 + falls in the follow-up period. Frequent fallers performed significantly worse than non-frequent fallers in the contrast sensitivity, reaction time and sway tests and had higher PPA composite scores. Conclusions: In line with poor PPA test performances, falls incidence in people with MS was high. This study provides comprehensive reference data for the PPA measures for people with MS that could be used to inform future research and clinical practice.